Produksi Animasi 2D “First Steps in Navy and Gray” Tentang College Adjusment Dimensi Sosial Untuk Mahasiswa Baru - Yoseph Satria Praka; Rifki Setiawan; Muhammad Ibnu Rosyid; Fahrur Ryu Pambudi; Fitria Nugrahani (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2026)
Higher education represents a transitional phase that requires freshmen to adapt academically and socially. However, many new students experience anxiety and difficulties in social adjustment during the early stages of college life. This study aims to develop a 2D animation as an informative and communicative educational medium addressing the social dimension of college adjustment for freshmen. The research employed an animation production method consisting of pre-production, production, and post-production stages, followed by alpha and beta testing. The beta testing results showed an actual score of 229 out of a maximum score of 280, with an overall evaluation index of 81.7%, indicating positive responses to the animation's visual quality, storytelling, and message delivery. The findings suggest that the developed 2D animation was well received by the respondents and has the potential to serve as an educational medium to support freshmen in understanding the process of social adjustment in the university environment.